Social Work Practice in Africa: A Bibliometric Analysis of Trends in Publications from 1963-2024 - Bah, Yahya Muhammed; Zengenene, Maybe; Gassama, Saikou; Zatrahadi, Muhammad Fahli; Istiqomah, Istiqomah (KONSELOR, 2024)
The development of this field in a varied and ever-changing regional context can be better understood by looking at the trajectory of social work in Africa from 1963 to 2024. The purpose of this study was to find out the trend of publications on social work in Africa from 1963 to 2024. Looking at the development of publications each year, the author of the most publications, the highest affiliations, and the most publications in journals on social work in Africa. Research methods use bibliometric analysis through scopus databases. There were 1305 publication documents found, and the data were downloaded in csv form without any form of limitation. Later, CSV data was included in the Vosviewers and Rstudio software to display images of visualization analysis results. The results show that research on social work in Africa spanning 1963–2024 revealed that this field has a variety of properties that reflect social and humanitarian responsibilities. By focusing on HIV/AIDS prevention, health, and management, social workers can help improve people's socioeconomic conditions and the overall quality of life in Africa.